Effects of Compound and Total Images on the Cohesion of in Al-Qahtani's Poetry - Bilal Khalid Khalaf; Othman Abdel Halim Jaalout; Ihab Majeed Mahmood (Nalans)
This article aims to explore the aesthetics of imagery in the poetry of Al-Qahtani, which can be categorized into two types: compound imagery resulting from the accumulation of images and compound imagery in narrative storytelling. Compound imagery is produced by accumulating carefully selected individual images to create a cascade of meanings. The second type encompasses narrative storytelling, either descriptive without dialogue or inclusive of narrative content within reading theory. This study offers a critical practice in light of reading theory regarding meaning issues that represent a complex problem with broad, intertwined and deep theoretical and practical dimensions. Selected poetic texts from the Southern Qahtani tradition are included in the study. The research methodology focuses on understanding the aesthetics of both compound and total imagery and their impact on the coherence of poetic texts. The study demonstrates how imagery serves as an artistic tool through which the poet conveys various themes, including conceptual perceptions, after projecting a sensory attribute onto them, allowing the conceptual to emerge with a sensory guise. Additionally, imagery encompasses sensory perceptions primarily arising from the poet’s sense of reality. This interconnection affords the poet ample freedom to express their imagery and present their ideas.